(untitled) (Revista de História Regional, 2007)
This article has the objective of presenting a case study about the practice of infanticide, as well as the treatment given to this practice in the judiciary of Ponta Grossa. Making the analysis of the law suits and presenting the different arguments of witnesses, relatives, doctors and the judge about the crime and the affective-sexual life of the defendant.